Monetizing new music ventures through blockchain: Four possible futures?. (November 2019) - O'Dair, Marcus; Owen, Robyn
The article examines the rapidly developing area of blockchain finance as a potential opportunity for new creative ventures to obtain external investment funding and generate revenues. We focus on the music industry, as an example of how alternative Internet-based finance utilizing blockchain could provide opportunities for start-up funding and ongoing revenue streams. Our pioneering pilot research findings are drawn from literature review and emerging case studies, and are grounded in the academic literature of start-up funding gaps. Although some expect blockchain technology to remove intermediaries, facilitating a direct relationship between artist and fan, initial findings are that intermediation in some form will remain. The article's central focus is the crucial emerging role of these facilitator organizations – the new breed of financial intermediaries or 'infomediaries'. We examine this evolving process through adoption and development of financial intermediation theory, exploring the wider financial intermediary concept of incubators and accelerators as expert investors and promoters of new and very early-stage ventures – including artists. The article poses the question of whether blockchain technology offers a new, more cooperative approach for creative ventures, or merely the reinvention of existing corporate structures, for instance, the three major record labels that currently dominate recorded music. The article identifies four possible paths for the adoption of blockchain technology within the music industry, ranging from the anarcho-libertarian to the corporate and from the 'utopian' to the 'dystopian'.